2014
DOI: 10.1021/ja411577t
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stable α-Synuclein Oligomers in the Molecular Events Underlying Amyloid Formation

Abstract: Studies of proteins' formation of amyloid fibrils have revealed that potentially cytotoxic oligomers frequently accumulate during fibril formation. An important question in the context of mechanistic studies of this process is whether or not oligomers are intermediates in the process of amyloid fibril formation, either as precursors of fibrils or as species involved in the fibril elongation process or instead if they are associated with an aggregation process that is distinct from that generating mature fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
352
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(402 citation statements)
references
References 82 publications
48
352
1
1
Order By: Relevance
“…Results show that high pressures available at the SAXS beamline -until 1.6 kbar -can subtly modify fibrils' sizes and density features, maintaining their overall morphological structure, and induce the fragmentation into soluble disordered aSN oligomers. The possible simultaneous presence of different oligomeric species, as recently detected and described in different experimental conditions by SAXS experiments [61,8,46], can be pointed up from our SAXS curves. Both wild type and familial mutants of aSN amyloid fibrils show that at increasing pressures the fraction of soluble disordered states is increasing.…”
Section: Saxssupporting
confidence: 68%
“…Results show that high pressures available at the SAXS beamline -until 1.6 kbar -can subtly modify fibrils' sizes and density features, maintaining their overall morphological structure, and induce the fragmentation into soluble disordered aSN oligomers. The possible simultaneous presence of different oligomeric species, as recently detected and described in different experimental conditions by SAXS experiments [61,8,46], can be pointed up from our SAXS curves. Both wild type and familial mutants of aSN amyloid fibrils show that at increasing pressures the fraction of soluble disordered states is increasing.…”
Section: Saxssupporting
confidence: 68%
“…This task has been hampered by the transient nature and inherent polydispersity of such species and the low amount they can be produced in vitro. Several methods have been developed to generate stable oligomers within a short time frame at the required yields to allow their characterization (13,14,28,30). These methods could lead to structurally and functionally distinct oligomeric species.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the experimental difficulties detailed above, some progress has been made on our current knowledge of the structure of oAS. Indeed, it has been demonstrated that oAS contain a substantial amount of non-fibrillar ␤-sheets (13,14) and that they are arranged in an antiparallel orientation (15,30 (17). In this work, we relied on the rational site-specific positioning of fluorescent tags along the protein sequence to obtain a more detailed representation of the internal architecture of oAS.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in good agreement with a recently performed SAXS study on oligomers formed under similar conditions in which the aggregation number was determined to be about 30 monomers per oligomer [81]. Additionally, we showed that for αS aggregation the fluorescent labels used do not have an influence.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…• C yielded a low-resolution structure of ellipsoidal shaped oligomers with a radius of about 4.5 nm and a radius to length ratio of about two [54,81] (see figure 1.5). In addition to these preparation protocols without any additional compounds present during aggregation, it has been shown that the morphology of αS oligomers is affected by molecular crowding [82] or by the addition of lipids [52,[65][66][67][68], or organic solvents [56,69], or metal ions [56,57,70].…”
Section: Morphologymentioning
confidence: 99%